Study of optimal design of parameters for spade punch planter of corn - Hua, Li Cheng (agricultural engineering.eu, 2001)
In accordance with the development of agricultural cultivation systems a punch planter with revolving spade working part for soil opening was designed for use on soils covered with plastic film and agricultural waste materials. For investigation of sowing quality the parameters of the punch planter vertical decline angle, horizontal decline angle and working speed were tested with three varieties of corn and the relation between parameters and sowing quality was analyzed.On the basis of experimental results and through regression analysis mathematical models describing sowing quality and its dependenceon the parameters were developed. With Computer-Aided Design (CAD) the optimal parameter for spade punch planting were calculated and the test results were satisfactory.